Analisis Semantik dan Hermeneutik terhadap Khantī dalam Syair Dhammapada 184: Menyingkap Makna Kesabaran dalam Buddhisme - Veni Sinto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study critically examines the semantic and symbolic depth of khanti (patience or forbearance) as expressed in Dhammapada verse 184: “Forbearance is the supreme ascetic practice (khanti parama tapo titikkhā), Nibbāna is supreme.” Through a qualitative hermeneutic approach that integrates classical semantics, modern linguistics, and Gadamerian interpretation, khanti is reinterpreted not merely as passive tolerance, but as an active moral and spiritual strategy within Buddhist ethical thought. The findings show that khanti functions as a multi-layered sign linguistically rich, symbolically resonant, and culturally embedded supporting inner transformation and ethical agency. In the Indonesian Buddhist context, khanti is reframed as a pedagogical and communicative tool for cultivating resilience, conflict resolution, and ethical leadership. This research contributes to interdisciplinary discourse on moral education and religious communication by emphasizing the strategic potential of Buddhist ethical concepts in contemporary society.